Santa Cruz de Guanacaste: cultura local, turismo y globalización - Morales Zúñiga, Luis Carlos (San José: Editorial Universidad de Costa Rica, 2009)
The article analyzes the relationship between local culture of the canton of Santa Cruz, Guanacaste, and the development of tourism in the canton. In a first section explores the origin and development of popular culture in the canton, linking it to traditional farming activities, then describes the deployment of tourism in Santa Cruz, in order to analyze the popular culture of the canton in a framework of productive activities ranging from farming to tourism, in a context of economic and cultural globalization.